Barriers to the Implementation of Alcohol Policies in Jayapura City - Rahel Violin Kamisorei; Mochammad Bagus Qomaruddin; Shrimarti Rukmini Devy; Amer Siddiq Amer Nordin (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2021)
Background: Basic Health Research (RISKESDAS) in 2018 found as many as 15 provinces out of 35 provinces had a prevalence of alcohol consumption above the national prevalence, and Papua was reportedly in the top 15 of the prevalence of high alcohol consumption (alcohol) as much as 4.6%. Objective: To describe the obstacles to the implementation of local government policies in curbing the circulation of alcohol in Jayapura City. Method: This is a descriptive study using a qualitative single instrumental case study design in Jayapura City from May to September 2020. Purposive sampling technique was employed to determine participants who consisted of an integrated team of alcohol control and supervision (n =6). Data collection was using in-depth interviews and non-participant observation. Result: Communication between the integrated team was not optimal. National Food and Drug Agency (BPOM) had not routinely conducted sample tests as the majority of traditional alcoholic beverages sold in shops such as local liquors were illegal. The division of duties and responsibilities by the integrated team was good, but the execution in the field was not as agreed upon. There were alcohol traders who have not applied for licenses to sell alcohol because the process to get license permits was too complicated. The content of Perda No.8 of 2014 weakened the police because they could not give punishment like Satpol PP, however, Satpol PP did not have an investigating team. Conclusion: The lack of commitment from the control and supervision team of alcohol circulation in carrying out their duties. The resources involved were lacking. Coordination among the integrated teams was not going well thus the division of tasks and authorities with implementation actions in the field did not work according to the policy enforce in Jayapura City. Evaluation of work programs by policy implementers could be carried out to increase the success of implementation.